Investigation of efficacy of an herbal product (Habb-E-Munish) in the treatment of ED Using IIEF-5 scores and its effect on liver and renal functions (Bangladesh Journal of Medical Science, 2019)
Background and Rationale: Incidence of erectile dysfunction is rising in both developing and developed countries including Bangladesh. Even in this 21st century people attracted to the herbal and/alternative medicine. The present study was aimed to evaluate the effect of Haab-e-Munish in the treatment using the International Index of Erectile Function-5 (IIEF-5) questionnaire.Material and Methods: A total 33 married male subjects participated in this study. The study was approved by the Research and Ethics Committee of the Ibn Sina Medical College & Hospital. Informed written consent was obtained from each participant. Data were expressed as mean±SD and were managed by SPSS for Windows Version 17. P